Choosing where to give birth: Factors influencing migrant women’s decision making in two regions of Thailand - Tschirhart, N; Jiraporncharoen, W; Angkurawaranon, C; Hashmi, A; Nosten, S; McGready, R; Ottersen, T (Public Library of Science, 2020)
Background: Choosing where to give birth can be a matter of life and death for both mother and child. Migrants, registered or unregistered, may face different choices and challenges than non-migrants. Despite this, previous research on the factors migrant women consider when deciding where to give birth is very limited. This paper addresses this gap by examining women’s decision making in a respective border and urban locale in Thailand.